Impact of the electric shock on the embryonic development and physiological traits in chicks embryo - ABDULATEEF, S M; ATALLA, O K; A L-ANI, M Q; MOHAMMED, T H T; ABDULATEEF, F M; ABDULMAJEED, O M (The Indian Journal of Animal Sciences, 2021)
The objective of this study was to investigate the impact of stimulating the embryo during the dormancy in the incubation period. 450 eggs (Ross 308) were allocated in four treatments each with three replicates. The treatments were as follows: T1 control (without shock), T2 Shocked (40) Millivolts (mV), T3 Shocked (50) (mV), T4 Shocked (75) (mV). A different voltage device was used to shock the egg, after marking the eggs with a line of iron filings to ensure electrical conductivity, eggs were shocked at different times three times a day. The results showed that the percentage of embryonic weight increased significantly and the percentage of albumin decreased significantly and the percentage of shells for experimental treatments during the seven days of incubation compared to the control treatment. The significant increase in the percentage of embryonic weight and amniotic sac and liquid and a significant decrease in the percentage of albumin and yolk compared to the control treatment at 14 and 17 days of incubation for experimental treatment. Significant increase in neurophysiological traits of neurons, brain weight for T2, T3 and especially T4 concluded that electrical stimulation had a positive effect on the embryo.